Evaluating Parameter Sharing for Spoofing-Aware Speaker Verification: A Case Study on the ASVspoof 5 Dataset - Buker, Aykut; Kurnaz, Oguzhan; Bekiryazici, Yule; Demirtac, Selim Can; Hanilci, Cemal (Isca-Int Speech Communication Assoc, 2025)
Spoofing-aware speaker verification (SASV) is an important but challenging task and has been a primary focus of the recently organized ASVspoof 5 challenge. As SASV integrates automatic speaker verification (ASV) and countermeasure (CM) systems, its performance depends on the effectiveness of each system. This study systematically examines the impact of different parameter-sharing (PS) strategies, which facilitate joint optimization, on SASV performance using the ASVspoof 5 dataset. Experimental results indicate that PS enhances performance for specific attack types and codec conditions. For example, the baseline system achieves a min a-DCF of 0.329 on the A26 attack, which improves to 0.233 with PS. Similarly, for AMR-compressed signals, PS yields a 14.09% performance gain. These observations show that PS techniques are effective in mitigating certain spoofing attacks and improving robustness to degraded audio conditions in SASV systems.
2025 Interspeech Conference -- AUG 17-21, 2025 -- Rotterdam, NETHERLANDS
Keywords: spoofing-aware speaker verification; parameter sharing; ASVspoof